Premises for Success of Corporate Social Responsibility Initiatives in Romania and the Students’ Perspectives - Cătălina RADU; Alecxandrina DEACONU; Ramona PUIA (Revista de Management Comparat International)
Corporate Social Responsibility (CSR) is becoming an ever more important component in the interaction between the business environment and the world in which companies operate. The term attracts interest from both people who apply it in their day-to-day activities and, also, from the academic field which is involved in its study, in order to help create future responsible managers. In order to familiarize ourselves with the current situation, we decided to determine the perception level students had in relation to this concept, not forgetting the fact that they might be employed in companies operating in this specific field and, also, that all of them are members of the community where these organizations function. Our study is based on the interpretation of a series of results extracted from a survey conducted by applying a questionnaire by using the online platform SurveyConsole. The study revealed numerous aspects previously deducted from our own observations, but there were also quite a few unexpected conclusions.